ANALISIS GERAK TEKNIK LOMPAT JAUH PADA ATLET KLUB GLADIATOR GRESIK - Rizki, Muhammad Faidhur; Irawan, Roy Januardi (Jurnal Kesehatan Olahraga, 2019)
Abstract The long jump is a combination of run, start, repulsion, time to drift, and landing. The purpose of this study is to find out the effective long jump movement technique of athletes at the Gresik district gladiator club. In this study, researchers used a type of non-experimental research with quantitative descriptive analysis research methods because this research was conducted because they wanted to know the motion analysis of the long jump technique in the Gresik gladiator club long jump athlete. This research is only limited to describing the motion video of the long jump technique from the start run to the athlete's landing position and notifying the measurement results related to the research. The instrument in this study was a camera that was used to record video when the gladiator club long jump athlete performed motion engineering exercises which were then processed using applications on a computer. The software used to analyze the recorded video is Kinovea. Based on the research that has been done, the results of the first subject research are producing the largest initial velocity of 12.04 m / s. The take-off angle is 36 °. The resulting power is 2611.75 watts, and the biggest jump is 6.85 m. In the second subject the largest initial velocity is 9.30 m / s. The resulting take-off angle is 31 °. The biggest power is 1638,275 watts, and the jump is 5.70 m. In the third subject, the largest initial velocity is 11.34 m / s. The take-off angle is 40 °. The biggest power produced is 2978.25 watts, and the jump is 6.18 m. In the fourth subject the result is the initial speed of 10.59 m / s. The take-off angle is 33 °. Power is 2070 watts, and the output is 6.60 m. Based on the research results of the long jump technique that has been carried out and discussed in the previous chapter, we can draw conclusions from this research, namely, a series of effective long jump techniques from the four athletes in the gladiator gresik club who have made 3 jumps, namely a series of technical moves from the first research subject to the third jump which at the same time became the leap with the farthest distance from all the jumps. Keywords: Kinovea, remote jump technique, Long jump technique biomechanics.